2021
DOI: 10.1097/md.0000000000026846
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of stroke severity with National Institutes of Health Stroke Scale grading and retinal features

Abstract: To estimate National Institutes of Health Stroke Scale (NIHSS) grading of stroke patients with retinal characteristics.A cross-sectional study was conducted in Shenzhen Traditional Chinese Medicine Hospital. Baseline information and retinal photos were collected within 2 weeks of admission. An NIHSS score was measured for each patient by trained doctors. Patients were classified into 0 to 4 score group and 5 to 42 score group for analysis. Three multivariate logistic models, with traditional clinical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(60 reference statements)
1
4
0
2
Order By: Relevance
“…As such, retinal fundus photography is an important tool for translational vascular research. [366, 389, 384, 385, 378, 379, 394, 401, 367, 405, 390, 408, 368, 369, 398, 380, 365, 406, 370, 386, 395, 399, 403, 391, 412, 371, 387, 407, 372-374, 381, 375, 67, 402, 410, 404, 392, 400, 409, 393, 413, 376, 382, 377, 397] Microvascular health 6 [389,378,401,396,388,383] Analysis Vascular Plethysmography…”
Section: Discussionmentioning
confidence: 99%
“…As such, retinal fundus photography is an important tool for translational vascular research. [366, 389, 384, 385, 378, 379, 394, 401, 367, 405, 390, 408, 368, 369, 398, 380, 365, 406, 370, 386, 395, 399, 403, 391, 412, 371, 387, 407, 372-374, 381, 375, 67, 402, 410, 404, 392, 400, 409, 393, 413, 376, 382, 377, 397] Microvascular health 6 [389,378,401,396,388,383] Analysis Vascular Plethysmography…”
Section: Discussionmentioning
confidence: 99%
“…Визначений наб ір даних про кожного з пацієнтів з МІ був внесений до спеціально створеної бази даних: вік, стать, тип і підтип МІ, оцінка тяжкості неврологічного дефіциту за інсультною шкалою Національних інститутів здоров'я (National Institutes of Health Stroke Scale (NIHSS)) та обмеження життєдіяльності за модифікованою шкалою Ренкіна (мШР). Відповідно до загальної оцінки за NIHSS виділено такі градації тяжкості МІ: легкий (0-5 балів), помірної тяжкості (6-13 балів), тяжкий (14-20 балів), дуже тяжкий (>20 балів) [22,23].…”
Section: матеріали та методи вибірка та умови проведення дослідженняunclassified
“…Considering the fact that there is no "gold standard" or universally recognized diagnostic criteria for SAP yet, the diagnosis of SAP was established by a pulmonologist or a internal medicine specialist based on clinical manifestations and the results of investigations (e.g., chest X-ray or multidetector spiral computer tomography), in accordance with the recommendations of the Centers for Disease Control and Prevention (Horan et al, 2008). According to the NIHSS total score, all cases were divided into mild (0-5), moderate (6-13), severe (14-20) and very severe (more than 20) CS (Zhuo et al, 2021). CS phases, depending on the time elapsed from the estimated CS onset to SC admission, were classified as hyperacute (0-24 hours), acute (1-7 days), early subacute (8 to 90 days), late subacute (91 to 180 days) and chronic (after 180 days) (Bernhardt et al, 2017).…”
Section: Aimmentioning
confidence: 99%
“…Previous studies have shown that SAP is associated with worse neurological and functional recovery and more than triples the risk of death (Armstrong & Mosher, 2011;Ingeman et al, 2011;Yuan et al, 2021). Despite the fact that reducing the risk of SAP could have a significant impact on CS outcome, effective medical (in particular, with antimicrobial agents) prevention of SAP has not yet been developed, and the risk factors of SAP in different periods of the disease have not been sufficiently studied (Grossmann et al, 2021;Liu et al, 2016;Zheng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%